Waste Evaluation in Crude Palm Oil (CPO) Production Using Lean Manufacturing Approach - Armijal; Marta, Ayu; Patrisina, Reinny; Hasan, Alizar; Amrina, Elita (TALENTA Publisher, 2025)
As business competition intensifies, an organization needs to streamline operations and improve plant performance, focusing on minimizing waste. At Company XYZ, inefficient processes have led to persistent waste in crude palm oil (CPO) production, particularly in the forms of motion, waiting, and transportation. The objective of this study is to identify waste in the CPO production, analyze its root causes, and propose actionable improvements. A lean manufacturing approach was employed using Value Stream Mapping (VSM), Waste Assessment Model (WAM), Waste Assessment Questionnaire (WAQ), Value Stream Mapping Tools (VALSAT), and Cause-and-Effect Diagram methodologies. The VSM analysis revealed motion, waiting, and transportation as the primary waste categories. Waste identification using WAM ranked motion as the most significant waste (19.39%), followed by waiting (14.91%), transportation (14.57%), overproduction (14.23%), defects (14.21%), inventory (14.17%), and overprocessing (8.52%). Process Activity Mapping (PAM) identified 34 activities, with 50% being value-added, 9% non-value-added, and 41% necessary but non-value-added. This research improves operational performance and productivity in CPO production using lean tools. These interventions are expected to reduce waste and enhance operational performance significantly.